On the Metric Dimension of Generalized Tensor Product of Interval with Paths and Cycles - Song Li; Jia-Bao Liu; Mobeen Munir (Journal of Mathematics)
The concept of minimum resolving set for a connected graph has played a vital role in Robotic navigation, networking, and in computer sciences. In this article, we investigate the values of m and n for which P2⊗mPn and P2⊗mCn are connected and find metric dimension in this case. We also conclude that, for each m, we obtain a new regular family of constant metric dimension. We also give a basis for these graphs and presentation of resolving vector in general closed form with respect to the basis.